The Development of Football Shooting Exercise Using The Back Feet of PS UNDHARI Players - Hendra Wawan Saputra; Dian Estu Prasetyo; Muhammad Sukron (The Future of Education Journal, 2022)
Someone to be able to have the skills to play well with the right technique or to be able to excel in the sport of soccer, many factors influence it. These factors are the quality of coaches, facilities and infrastructure, training programs, mastery of basic techniques, the ability of physical, mental conditions, parental support and so on, as well as for UNHARI soccer athletes in having achievements in the soccer sport branch. This research is a research and development Research and Development R&D that aims to produce new products from the results of development using the ADDIE model which consists of 5 stages, namely, analysis (analyze), design (design), development (development), implementation (implementation), evaluation ( evaluation). The five stages are carried out through analysis of player needs and analysis of player characteristics. Then the validation test was carried out by 4 validators (expert teams), practicality tests by football coaches and 14 players, after the model was categorized as valid and practical, then the effectiveness test was carried out. The validity of the soccer shooting practice model was assessed by four validators, indicating that the shooting practice model obtained an average percentage of 86% with a very valid category, so it can be concluded that this shooting development model is feasible to use. Practicality assessed from the trainer's response questionnaire with a percentage of 90% in the very practical category and the player response questionnaire with a percentage of 87% in the practical category, it can be concluded that the soccer shooting practice model is easy to use for UNDHARI PS players. The effectiveness assessed from shooting practice obtained a percentage of 71.4% with an effective category so that the use of the soccer shooting practice model was able to achieve the desired training objectives